Dispersive liquid‐liquid microextraction coupled with pressure‐assisted electrokinetic injection for simultaneous enrichment of seven phenolic compounds in water samples followed by determination using capillary electrophoresis. Issue 13 (6th May 2019) - Ma, Suya; Gao, Fangfang; Lu, Wenhui; Zhou, Na; You, Huiyan; Li, Jinhua; Chen, Lingxin
Abstract: Offline dispersive liquid‐liquid microextraction combined with online pressure‐assisted electrokinetic injection was developed to simultaneously enrich seven phenolic compounds in water samples, followed by determination using capillary electrophoresis, namely phenol, 4‐chlorophenol, pentachlorophenol, 2, 4, 6‐trichlorophenol, 2, 4‐dichlorophenol, 2‐chlorophenol, and 2, 6‐dichlorophenol. Several parameters affecting separation performance of capillary electrophoresis and the enrichment efficiency of pressure‐assisted electrokinetic injection and dispersive liquid‐liquid microextraction were systematically investigated. Under the optimal conditions, seven phenolic compounds were completely separated within 14 min and good enrichment factors were obtained of 61, 236, 3705, 3288, 920, 86, and 1807 for phenol, 4‐chlorophenol, pentachlorophenol, 2, 4, 6‐trichlorophenol, 2, 4‐dichlorophenol, 2‐chlorophenol, and 2, 6‐dichlorophenol, respectively. Good linearity was attained in the range of 0.1–200 μg/L for 2, 4‐dichlorophenol, 0.5–200 μg/L for 4‐chlorophenol, pentachlorophenol, 2, 4, 6‐trichlorophenol, 2‐chlorophenol, and 2, 6‐dichlorophenol, as well as 1–200 μg/L for phenol, with correlation coefficients ( r ) over 0.9905. The limits of detection and quantification ranging from 0.03–0.28 and 0.07–0.94 μg/L were attained. This two step enrichment method was potentially applicable for the rapid and simultaneous determination of phenolic compounds in water samples.